Computer organization & architecture with MIPS programming: lab companion - Ayop, Zakiah; Anawar, Syarulnaziah; Ramly, Marliza; Hassan, Aslinda (Penerbit UTeM Press, 2013)
A survey of computer configuration and display technology. Things to consider before buying a computer. General item and specification on the computer. Choosing the best computer brand and price. General computer parts and specifications for a personal computer.